GUIDELINES FOR THE EFFECTIVE USE OF THE “TRAVEL AROUND UZBEKISTAN” PROGRAM IN THE DEVELOPMENT OF LOCAL TOURISM - TUKHLIEV ISKANDAR SUYUNOVICH; RAHIMOVA MOHINUR JALOLIDDINOVNA (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the article, studies were conducted on the directions of effective use of the "Travel around Uzbekistan" program in the development of local tourism. Also, proposals are made on improving the organizational and economic mechanisms of the organization and development of local tourism in Uzbekistan based on innovative approaches.